International Law and Argumentation: Navigating Constraints and Seeking New Orientations - Haidar, Ronnie (Informal Logic)

(untitled) (Informal Logic, 2025)
It is widely recognized in legal scholarship that international law functions as an argumentation practice, but its purpose remains debated. Some argue it legitimizes legal facts, while others believe it persuades actors to adopt specific positions. I align with Harald Wohlrapp's argumentation theory, which focuses on acquiring new orientations. I will outline why Wohlrapp's theory suits international law by examining three elements: prioritizing validity over mere assent, introducing "midrange universality" that balances community perspectives with a universal outlook, and introducing "framing" to responsibly integrate diverse cultural and legal perspectives, including those from the Third World Approaches to International Law (TWAIL).